Etika Komunikasi Pada Anggota Official Account Draft Sms Di Media Sosial - Nadya Surya Shindhita; Mukaromah Mukaromah (Fakultas Ilmu Komunikasi UKWMS, 2020)
Misunderstandings is often unavoidable in social media because users do not interact face-to-face. Non-verbal responses are often invisible. The emergence of several cases about unethical post are the basis of this research. The official account line named Draft SMS became an interesting virtual discussion room because it offers the advantages of expressive emoticon features; which is prominent to reduce the distortion of the message's meaning. Every interaction conducted in a virtual space should apply ethics as a guide in communicating to minimize these misunderstandings. The purpose of this study is to find out how the meaning of messages to communication actors when interacting in virtual space and communication ethics. The theory used in this research is Symbolic Interactionism and Communication Ethics. Using a qualitative approach with the Virtual Ethnographic method. The result that can be obtained is the meaning that occurs in the virtual interaction space shows that the need for a deeper understanding between the actors of communication so as not to cause misinterpretation of the messages sent by the sender so as not to cause divisions and ethical violations. Need control and self-control in each of them for the information received and then commented on.